2010
DOI: 10.1001/archinternmed.2010.301
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Cost-effectiveness of a 3-Year Trial of Lifestyle Intervention in Primary Health Care

Abstract: Lifestyle intervention in primary care improves QOL and is highly cost-effective in relation to standard care. Trial Registration clinicaltrials.gov Identifier: NCT00486941.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 31 publications
5
49
1
1
Order By: Relevance
“…Similar result was shown by Corby K Martin et al 2009 found significant improvement in all dimension of quality of life with exercise in sedentary postmenopausal women and improvements in quality of life were dose dependent [52]. Margareeta k Eriksson et al 2010 also found improvement in physical functioning and social functioning and reduced body pain with exercise and dietary counselling in CVD patient [53].…”
Section: Health Related Quality Of Life (Hrqol)supporting
confidence: 62%
“…Similar result was shown by Corby K Martin et al 2009 found significant improvement in all dimension of quality of life with exercise in sedentary postmenopausal women and improvements in quality of life were dose dependent [52]. Margareeta k Eriksson et al 2010 also found improvement in physical functioning and social functioning and reduced body pain with exercise and dietary counselling in CVD patient [53].…”
Section: Health Related Quality Of Life (Hrqol)supporting
confidence: 62%
“…Studies (29–33) in the general population demonstrated a positive effect of physical activity on health status, physical fitness, and various metabolic measures. Randomized controlled trials (RCTs) (3441) among adults with chronic conditions have shown a positive effect of interventions aimed to increase physical activity and incremental benefit in QALY outcomes. Change in QALY between intervention and control groups in these trials have been reported to range from 0.01 to 0.13 over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] These interventions can also be successfully implemented in a cost-effective way in primary care settings to reduce CVD risk and to improve quality of life. 131 Pedometer programs and mass media-based community campaigns have been found to be the most cost-effective, whereas general practitioner referral to an exercise physiologist was the least cost-effective because of travel costs and the associated time spent on consultation and screening. 127 A behavior-based intervention in which participants were taught to integrate daily moderately vigorous physical activity into their lives was found to be more cost-effective than a structured exercise program for improving physical activity and cardiovascular health.…”
Section: Physical Activitymentioning
confidence: 99%